Václav Horčička, Jan Němeček, Marija Wakounig, Vojtěch Kessler, Jaroslav Valkoun - "The Frustrated Peace?: The Versailles Treaty and its Political, Social and Economic Impact on Europe", Beč-Hamburg, 2021 - Krpić, Amir (Historical Thought, 2025)